In the house of the law : gender and Islamic law in Ottoman Syria and Palestine - Tucker, Judith E. (University of California Press, 1998)
"In the House of the Law examines how law, in both theory and practice, shaped gender roles in Palestine and Syria during the seventeenth and eighteenth centuries. It was a time during which Muslim legal thinkers gave a great deal of attention to women's roles in society. Challenging prevailing views on Islam and gender as well as contemporary Islamist interpretations of the tradition, Judith Tucker shows that Islamic law was more fluid and flexible than previously thought." "Using primary materials previously unmined by scholars, including the fatwas of prominent jurists and the Islamic law, or sharia, records of three Islamic courts - Damascus, Jerusalem, and Nablus - Tucker explores the ways in which Islamic legal thinkers and the court system understood the message of Islam for women and gender relations. By examining court cases on marriage, divorce, childrearing, and sexuality, Tucker sheds light on the relations between men and women, parents and children in the societies of those times."--Jacket